2001
DOI: 10.2307/3345865
|View full text |Cite
|
Sign up to set email alerts
|

Authentic-Context Learning Activities in Instrumental Music Teacher Education

Abstract: The purpose of this study was to examine the relationship between the frequency of particular authentic-context learning (ACL) activities during undergraduate instrumental music teacher training and the initial teaching performance (ITP) of undergraduate instrumental music student teachers. Subjects (N = 30) were instrumental music student teachers at four major universities. Four ACL activities, identified from the literature and limited to instrumental music settings, included (a) early field experience teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 6 publications
6
52
1
Order By: Relevance
“…Similar results were found for the correlation of ACL activities on teacher effectiveness in undergraduate instrumental music student teachers (Haston & Russell, 2012;Paul et al, 2001). Conducting teachers may want to consider providing beginning conducting students with multiple opportunities to apply their skills in front of a live ensemble, but not just during class meetings.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results were found for the correlation of ACL activities on teacher effectiveness in undergraduate instrumental music student teachers (Haston & Russell, 2012;Paul et al, 2001). Conducting teachers may want to consider providing beginning conducting students with multiple opportunities to apply their skills in front of a live ensemble, but not just during class meetings.…”
Section: Discussionsupporting
confidence: 73%
“…Perhaps instruction provided during the initial three semesters of one's degree program may offer the foundation needed to sustain an effect. Similar to the results of Paul et al (2001), perhaps there are a critical number of experiences beyond which music teacher role development becomes self-sustaining. Additionally, it is important to consider that students reaching upper division coursework do not include those who had previously self-selected out of the program.…”
Section: Discussionsupporting
confidence: 67%
“…It is possible instructional skills developed in the teacher role development training course were sufficiently mitigated by the passage of time to bring members of Group 2 on par with members of Group 1 by the time the present study was conducted. Paul et al (2001) found those with a greater number of peer teaching experiences, field teaching experiences, and reflections on those experiences scored higher on initial teaching performance than did those with fewer such experiences. Perhaps the number of peer teaching experiences and reflections on those experiences provided in the role development training course was not sufficient to affect initial teaching performance.…”
Section: Teaching Effectivenessmentioning
confidence: 86%
See 1 more Smart Citation
“…Given the increased volume of published research on mentoring, teacher identity, preservice teaching experience, and authentic learning contexts (Austin, Isbell, and Russell 2012;Berg 2010;Bouij 1998;Haston and Hourigan 2007;Haston and Russell 2012;Kruse 2011;Paul et al 2001;Robbins 1993;Thompson and Campbell 2010;Woodford 2002), it seems appropriate to outline the details of a comprehensive policy of music education training for multiple music education constituents. The long-standing de facto segregation of constituents by teaching level is outdated and counterproductive, regardless of role.…”
Section: A Music Education Policy To Facilitate Multiple Constituent mentioning
confidence: 98%